Identification of the Dimensions and Components of the Social Integration Model Based on Reducing Risk Behaviors in Women Recovering from Addiction in Tehran - Shams Ehsan, Zahra; Shiri, Tahmures; Mansourlkoorej , Mohammad Hadi (Psychology of Woman Journal, 2025)
Objective: The aim of this study was to identify the dimensions and components of the social integration model based on reducing risk behaviors in women recovering from addiction in Tehran. Methods and Materials: Given the study’s objective, the research is applied, and its methodology is qualitative. The statistical population of this research includes 10 experts and specialists in the field of social sciences who have conducted research at universities, as well as experts in social sciences, psychiatry, cyber-police managers, the Drug Control Headquarters, and others. A purposive non-random sampling method was employed. Data collection was conducted through semi-structured interviews. Data analysis was carried out using NVivo12 software. Findings: Based on the conducted analysis, 15 categories were identified and confirmed. The identified categories include family support, social acceptance, economic empowerment, access to psychological services, physical health support, life skills training, participation in cultural and social activities, support and participation of non-governmental organizations, sustainable housing facilities, vocational and technical training, creating a sense of identity and personal value, government support programs, rehabilitation and reintegration facilities, support groups, and self-help, as well as regular monitoring and follow-up. Conclusion: This study highlights key social integration factors for reducing high-risk behaviors, emphasizing the importance of family support, access to psychological services, and economic empowerment in fostering social reintegration and resilience.